Merdeka Belajar Episode 6: Transformasi Dana Pemerintah untuk Pendidikan Tinggi - Reva Aditya Puteri (Journal of Information Systems and Management (JISMA), 2024)
This article aims to shed light on the transformation of government funding for higher education. This study uses a descriptive qualitative method by noting because the data source was obtained by listening to oral narration from the YouTube channel of the Ministry of Education and Culture of the Republic of Indonesia entitled "Merdeka Belajar Episode 6: Transformation of Government Funding for Higher Education" This article focuses on the discussion of the allocation of Government Funds for Higher Education. The purpose of this article is that Universities should loosen their curricula from rigid to flexible and open themselves up to new methods. Higher education must be more responsive to existing challenges, (changing) from a theoretical approach to a problem-solving approach to be able to create a positive impact